The Development of Leadership Style of Chief Village Based on Local Wisdom "Asta Brata" in Buleleng Regency - Ni Luh Putu Eka Yudi Prastiwi; Luh Kartika Ningsih (Journal of Business on Hospitality and Tourism, 2020)
The purpose of this study was to determine how the leadership of Asta Brata of the Chief Village and Leader Member Exchange was able to influence the performance of village apparatus in Buleleng Regency. This study used an associative quantitative method. The data analysis technique used in this study is a variance-based structural equation modelling (SEM) or component based SEM, which is known as Partial Least Square (PLS) Visual version 3.0. All the relationships studied showed positive and significant results. In its realization, Asta Brata’s leadership is able to improve the performance of village apparatus. Likewise, the Leader Member Exchange is able to increase the Performance of Village apparatus. The indicators that show the highest score are Kwera Brata and Loyalty, the combination of these indicators is a strong benchmark in improving the performance of village apparatus in Buleleng Regency.